Question
upstudy study bank question image url

A \( -13 x+12=13 x+13 \) B \( -13 x+12=13 x-13 \) \( 12 x+12=13 x+12 \) (D) \( 12 x+12=13 x-12 \)

Ask by Ross Sandoval. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are: A. \( x = -\frac{1}{26} \) B. \( x = \frac{25}{26} \) C. \( x = 0 \) D. \( x = 24 \)

Solution

Solve the equation \( -13x+12=13x+13 \). Solve the equation by following steps: - step0: Solve for \(x\): \(-13x+12=13x+13\) - step1: Move the expression to the left side: \(-13x-13x=13-12\) - step2: Add and subtract: \(-26x=13-12\) - step3: Add and subtract: \(-26x=1\) - step4: Change the signs: \(26x=-1\) - step5: Divide both sides: \(\frac{26x}{26}=\frac{-1}{26}\) - step6: Divide the numbers: \(x=-\frac{1}{26}\) Solve the equation \( -13x+12=13x-13 \). Solve the equation by following steps: - step0: Solve for \(x\): \(-13x+12=13x-13\) - step1: Move the expression to the left side: \(-13x-13x=-13-12\) - step2: Add and subtract: \(-26x=-13-12\) - step3: Add and subtract: \(-26x=-25\) - step4: Change the signs: \(26x=25\) - step5: Divide both sides: \(\frac{26x}{26}=\frac{25}{26}\) - step6: Divide the numbers: \(x=\frac{25}{26}\) Solve the equation \( 12x+12=13x+12 \). Solve the equation by following steps: - step0: Solve for \(x\): \(12x+12=13x+12\) - step1: Cancel equal terms: \(12x=13x\) - step2: Add or subtract both sides: \(12x-13x=0\) - step3: Subtract the terms: \(-x=0\) - step4: Change the signs: \(x=0\) Solve the equation \( 12x+12=13x-12 \). Solve the equation by following steps: - step0: Solve for \(x\): \(12x+12=13x-12\) - step1: Move the expression to the left side: \(12x-13x=-12-12\) - step2: Add and subtract: \(-x=-12-12\) - step3: Add and subtract: \(-x=-24\) - step4: Change the signs: \(x=24\) The solutions to the given equations are: A. \( -13x+12=13x+13 \) has the solution \( x = -\frac{1}{26} \). B. \( -13x+12=13x-13 \) has the solution \( x = \frac{25}{26} \). C. \( 12x+12=13x+12 \) has the solution \( x = 0 \). D. \( 12x+12=13x-12 \) has the solution \( x = 24 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the equation \( -13x + 12 = 13x + 13 \), you first want to get all terms involving \( x \) on one side and constant terms on the other. By adding \( 13x \) to both sides, you obtain \( 12 = 26x + 13 \). Subtracting \( 13 \) from both sides gives you \( -1 = 26x \), leading to \( x = -\frac{1}{26} \). Moving on to \( -13x + 12 = 13x - 13 \), after simplifying similarly, you’ll find \( 25 = 26x \) or \( x = \frac{25}{26} \). Now, for \( 12x + 12 = 13x + 12 \), you can quickly see that the constants cancel out, leaving you with \( 12x = 13x \), which implies \( 0 = x \). Finally, with \( 12x + 12 = 13x - 12 \), isolating \( x \) results in \( 24 = x \). Each equation has a different unique solution, providing a fun challenge in algebraic manipulation! Each equation shows how balancing is essential in algebra—understanding that moving terms around doesn't change the truth of the equation! Balancing equally on both sides prevents errors commonly made when terms are misplaced or skipped. So grab a pencil and test your skills, because creating equations can be as exhilarating as unearthing hidden treasures in mathematics!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy